Micropropagation and pigment extraction of Echinocereus cinerascens / Hashimah Elias - Hashimah, Elias (2017)
Protocols were successfully established for in vitro regeneration and coloured callus production of Echinocereus cinerascens. Investigation mainly focused on the effects of plant growth regulators in rapid production of this endangered species and the optimum production of coloured callus. Additional assessments studied concerning the production of synthetic seeds, extraction of natural pigments and detection of somaclonal variation of the regenerants. Rapid production through direct in vitro regeneration gave the highest mean number of shoots, 4.37 ± 0.27, observed in MS medium supplemented with 2.0 mg/l Kinetin + 1.0 mg/l IBA which promoted the highest production of shoots after 4 months, 131 shoots in total. Nevertheless, through indirect in vitro regeneration, somatic embryos of Echinocereus cinerascens were successfully developed in two treatments of liquid medium including MS medium supplemented with 0.5 mg/l 2,4-D + 0.1 mg/l BAP + 0.5 mg/l thiamine HCl and MS medium supplemented with 0.5 mg/l 2,4-D + 0.5 mg/l BAP + 0.5 mg/l thiamine HCl, as both media promoted 100% total mean production of somatic embryos (globular, heart, torpedo-shaped and cotyledonary stage) after 4 months. Practically, the production of ideal synthetic seeds was successfully established whereby, micro shoots as the most responsive propagule were encapsulated in 3% of sodium alginate hardened in 100 mM of calcium chloride dehydrate solution for 30 minutes gave 100% of germination rate after 4 months. Complete plantlets were successfully acclimatized with the highest survival rate of 90% observed in sand, the most suitable planting substrate which possessed 3 major elements such as SiO2, Al2O3 and CaO that play important roles to support the growth of Echinocereus cinerascens. Basically, the present study indicated that 100% production of green, yellow and pink callus was obtained after 2 months in several treatments of MS medium supplemented with 2,4-D + BAP + thiamine HCl applied in combination. Interestingly, the occurrence of dramatic changes in the production of coloured callus was clearly observed in a conversion of green to pink callus within 2 months. Moreover, pigment extraction analysis through UV-VIS spectroscopy discovered that both regenerants and callus possessed chlorophyll a and b as the major pigment while carotenoids as the minor pigment. Meanwhile, HPLC analysis revealed individual carotenoids present in in vitro plantlets namely, neoxanthin, β-carotene, lutein and violaxanthin, whereas in callus were β-carotene and lutein only. Analysis of cytological studies clarified that there were no significant differences in cell organization and behaviour of in vitro plantlets and ex vitro plants. The evidence verified that Echinocereus cinerascens regenerated normally in vitro and grown vigorously after being transferred to the natural environment